German vector in the creative herritage of Wislawa Shymborska (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article is devoted to defining the role of German theme in the poetry of Wislawa Szymborska creative features. The author of the article made comparative analysis of some elements of the poetics of Polish writer and the German poet Heinrich Heine. Determine the total and perfect in the use of poetic literature of the two writers, revealing the theme of love.
Keywords: poetics; spirituality; irony; love theme; a subtext